2011
DOI: 10.1111/j.1471-4159.2011.07496.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomes accumulation is associated with β‐amyloid deposits and secondary damage in the thalamus after focal cortical infarction in hypertensive rats

Abstract: J. Neurochem. (2012) 120, 564–573. Abstract Focal cerebral cortical infarction after distal middle cerebral artery occlusion causes β‐amyloid deposition and secondary neuronal degeneration in the ipsilateral ventroposterior nucleus of the thalamus. Several studies suggest that autophagy is an active pathway for β‐amyloid peptide generation. This study aimed to investigate the role of autophagy in thalamic β‐amyloid deposition and neuronal degeneration after cerebral cortical infarction in hypertensive rats. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…45 We investigated the role of macroautophagy in the secondary thalamic degeneration after cerebral cortical infarction in rats and found that macroautophagy was activated in the ipsilateral thalamic cells. 46,47 Furthermore, macroautophagic inhibitor and Beclin-1 knockdown significantly reduced the macroautophagic activation and neuronal loss, suggesting macroautophagy may act in cell death in secondary thalamic degeneration. 46,47 To further understand the role of macroautophagy in secondary degeneration, it is necessary to investigate exactly how macroautophagy contributes to cell death and its relationship with other cell death pathways.…”
Section: Macroautophagymentioning
confidence: 93%
See 1 more Smart Citation
“…45 We investigated the role of macroautophagy in the secondary thalamic degeneration after cerebral cortical infarction in rats and found that macroautophagy was activated in the ipsilateral thalamic cells. 46,47 Furthermore, macroautophagic inhibitor and Beclin-1 knockdown significantly reduced the macroautophagic activation and neuronal loss, suggesting macroautophagy may act in cell death in secondary thalamic degeneration. 46,47 To further understand the role of macroautophagy in secondary degeneration, it is necessary to investigate exactly how macroautophagy contributes to cell death and its relationship with other cell death pathways.…”
Section: Macroautophagymentioning
confidence: 93%
“…Inhibition of macroautophagy prevented the A␤ accumulation and, conversely, reduction of A␤ suppressed macroautophagy activation. 46,47 Future studies are needed to elucidate the underlying mechanisms.…”
Section: Macroautophagymentioning
confidence: 99%
“…The area immediately outside of this zone is referred to as the “peri-infarct”, in which most neurons do not display the histological signs of irreversible damage [34]. The volumes of the ipsilateral and the contra-lateral hemisphere were counted as described previously [3,35,36] and the relative infarct volume was described as a percentage of the contra-lateral hemisphere. All the mNSS, infarct size calculation and immunostaining quantitation were performed blinded, which were reviewed and analyzed separately by two independent researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations on this injury model have been made using 3MA to assess the involvement of autophagy in neuronal death. (Wen et al 2008;Puyal et al 2009;Piras et al 2011;Wang et al 2011;Xin et al 2011;Zhang 2012). Beneficial effects of autophagic inhibition have also been seen in several models of chronic neurodegenerative diseases.…”
Section: Autophagy Overactivation-an Uncommon Cell Death Pathway In Nmentioning
confidence: 99%